Edukasi Potensi Kebencanaan dan Upaya Mitigasi Bencana Alam Melalui Kelas Inspirasi Kebumian di Sumbermanjing Wetan, Kabupaten Malang - Maryadi; Fenny Prawita Sari; Siti Aisyah Aulia; Muhammad Haris Miftahul Fajar; Juan Pandu Gya Nur Rochman (Sewagati, 2026)
Sumberagung Village, Sumbermanjing Wetan Subdistrict, Malang Regency, is located in an active fault zone running northwest-southeast (NW-SE), making it highly vulnerable to earthquakes and landslides. This condition requires an increase in community disaster literacy through a geoscience-based educational approach. This community service activity aims to increase the understanding and preparedness of the community, especially students, regarding potential geological hazards through the Earth Inspiration Class program. The implementation methods include surface geological mapping, gravity surveys, and magnetic measurements to identify subsurface structures and active fault zones in the study area. The survey results were integrated into interactive learning media delivered through lectures, discussions, and visual demonstrations. Based on the evaluation results, the average understanding score of the participants reached 72.41 out of 100, indicating a significant increase in geoscience literacy and disaster mitigation awareness. This program has proven effective in introducing geoscience concepts in a contextual and applicable manner, while encouraging active community participation in disaster risk reduction efforts. This activity is expected to become a model for sustainable geoscience-based disaster education in other disaster-prone areas.